Experimental investigation of changes in petrophysical properties during CO2 injection into dolomite-rich rocks. (April 2017) - Khather, Mohamed; Saeedi, Ali; Rezaee, Reza; Noble, Ryan R.P.; Gray, David
Highlights: Mechanisms of mineral dissolution/precipitation and mechanical compaction control post-flood properties of carbonates. Original textural features and core-scale heterogeneities influence the response of a sample to flooding process. The porosity and permeability of the post-flood samples could increase or decrease depending on which of the mechanisms are dominant. Wormholes and dissolution features may be created at the inlet region of the samples. Abstract: Carbon dioxide may be injected into an underground geological structure for mere geo-sequestration purposes or as a means of enhanced hydrocarbon recovery. During such an operation, CO2 is expected to dissolve in the in-situ fluids (primarily consisting of brine) generating a reactive in-situ solute (i.e. carbonated brine). Subsequently, a series of consecutive chemical reactions may occur between the solute and the host rock. While these reactions are generally known from a qualitative perspective, to what extent they may impact on the host formation's petrophysical properties requires extensive evaluation on a case by case basis. Due to the presence of highly reactive minerals in their composition, carbonate rocks (e.g. dolostone) present a more complex system to evaluate in terms of the above mentioned chemical reactions. This experimental study has been carried out to evaluate changes in the petrophysical properties of a number of heterogeneous dolostone samples after undergoing carbonated brine flooding under in-situ reservoir conditions. In this study, the core-flood experiments are complemented by pre- and post-flood porosity, permeability and NMR (nuclear magnetic resonance) measurements, X-ray CT scanning and X-ray Diffraction (XRD) and Energy-Dispersive X-ray (EDX) analysis. Overall, a slight increase in the porosity was observed in most samples, most likely, caused by the dissolution of dolomite (CaMg(CO3 )2 ), calcite (CaCO3 ) and/or anhydrite (CaSO4 ). The results also show an increase in the permeability of some samples which again could be attributed to dissolution of the minerals. The X-ray CT images show signs of excessive dissolution of minerals and the creation of dissolution patterns (i.e. wormholes). On the other hand, reductions in permeability and porosity by 57% and 12%, respectively, were also observed in a sample. This is believed to be due to the combined effects of the mineral precipitation and mechanical compaction mechanisms dominating over the mineral dissolution. A small shift in the pore size distribution of the samples towards smaller pore sizes was also observed which is believed to have been caused by mechanical compaction.